Dependence of Elastic Deformations of Spindle-Tool Subsystem on Influence of Cutting Force Radial Component - Kazakova O. Yu. (EDP Sciences, 2021)
The results of field research are presented in the article. The parameters that affect the position of the tool in the spindle of the machine are determined. The tasks concerning the identification of the angular position of the tool in the spindle are solved. The issues of the influence of the cutting force radial component on elastic angular deformations in the spindle and tool contact area are considered.